Influences Of Indonesian Vernacular Languages On Students’ English Pronunciation - Melisca Andriani (UKMC International Conference (UKMC IC) Proceedings, 2024)
Vernacular languages are informal and unstandardized forms of a language that are spoken locally within a particular region or community. This also can have an influence on the process of teaching English pronunciation. Pronunciation is defined as the way in which a language is spoken, specifically the way in which a word is pronounced, or the way a person speaks the words of a language. This article aims to discuss in depth whether vernacular language has an influence on students' English pronunciation. This study explores the influence between vernacular language and English pronunciation and whether the two are related. Specifically discussing Indonesian students who have vernacular language and seeing whether they find it difficult because their vernacular language has an impact on learning English pronunciation. This study uses quantitative methodology and to gain the data, the study used a questionnaire as an instrument. Based on the answers from the participants, we can conclude that the participants feel that vernacular language does not influence their English pronunciation. There are some factors that may influence the students' pronunciation, but in this study most participants felt that their vernacular language had no influence on their English pronunciation.